THE EFFECTS OF PROLONGED ECONOMIC STRESSORS IN MINORITY LOW-INCOME NEIGHBORHOODS ON FAMILY FUNCTIONING AND CHILD DEVELOPMENTAL OUTCOMES (Proceedings of the International Conference on Poverty and Sustainable Development, 2019)
Poverty and prolonged periods of unemployment have been shown to affect the ability of families to function as evidenced by effective parental interaction and child developmental outcomes. Minority families, particularly African-Americans and Latinos, are more likely to live in urban neighborhoods characterized by concentrated poverty, than Caucasians.  This paper explores the inter-relationship between federal welfare policy, institutional barriers such as housing discrimination, as well as banking practices, on family stability in minority low income neighborhoods. The unintended consequences of neighborhood segregation on family functioning and child developmental outcomes, neighborhood violence, and barriers to upward mobility to more stable neighborhoods are examined.  Three models which explore the dynamics of economic stressors within the family unit, the impact on cognitive and psychological development of the child and the role of effective parental/child interactive strategies in light of profound economic hardship are presented.  Finally, this paper covers research on the underlying dynamics of concentrated urban poverty on marital/family stability and recommends policies to promote family resiliency.
Keywords: poverty; policy; family; hardship